PEMANFAATAN DAUN LAMTORO DALAM PAKAN AYAM PETELUR DI PETERNAKAN DUSUN WARINGIN CAP - Ralahalu, Tabita Naomi; Malle, Dominggus; Joris, Lily (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Most of the population of Waringin Cap are farmers construction workers, and a small portion are breeders. Government support conditioned one farmer to receive assistance for 700 laying hens, divided into two, 250 each, after the unavoidable loss of 200 chicks. The production of kept chicken eggs does not meet the requirements because they are constrained by the feed supply, both in quality and quantity. Community service activities aim to increase the knowledge and abilities of breeders regarding the use of natural resources around the livestock location to be used as feed ingredients. Community service activities in Waringin Cap hamlet have several solutions, namely an approach with the hamlet government and partner breeder groups regarding the aims and objectives of implementing the science and technology implementation program, implementing counseling, and asking questions about various practical knowledge related to the primary factors, namely feed and its provision, distributing brochures on problems and solutions for improving feed formulas and demonstration plots for laying hen feed formulas. Improving feed using lamtoro leaves is one way that can help farmers meet livestock needs. Community service activities have received good appreciation from farmers because they provide new information for breeders to improve the quality of feed provided so that they can increase egg production.